Pedagogical Beliefs and Intention of Teaching Using ICT in Uganda’s Higher Education Institutions - Watsemba , Aisha Namome; Moya , Musa B.; Mugisha , Donatus (University of Dar es Salaam Library Journal, 2024)
Though COVID-19 restrictions demonstrated the relevance of using Information Communication Technology (ICT) in education, academic staff are hinged to engage in face-to-face teaching as well as holding on to other related teaching methods associated with how they were taught, how colleagues teach, and even their perception of past successful teaching modes, thereby limiting ICT usage in the lecturing process in Higher Education Institutions (HEIs) in Uganda. This study was carried out to establish the relationship between pedagogical beliefs and behavioral intention to teach using ICT in HEIs in the country. This focus was derived from the realization that pedagogical beliefs are manifested through modes of provision of lectures and the mode of interaction between academic staff and students, which have the potential to trigger the behavioral intention to use ICT in teaching in the HEIs in Uganda. This study centered on three representative HEIs in Uganda; Makerere University, Kyambogo University, and Makerere University Business School. A survey technique was used to collect data from a sample of 322 academic staff members out of a population of 1,916. Correlation and regression analyses were used to analyze the collected data. Findings indicated that pedagogical beliefs, specifically “interaction between students and lecturers,” had a significant association with and influence behavioral intention to use ICT for teaching in HEIs in Uganda. Therefore, it is recommended that academic staff members' and students' views be considered before selecting whether to use ICT in the teaching process in HEIs in Uganda.